2019
DOI: 10.1088/1742-6596/1410/1/012096
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of current-voltage characteristics and power-voltage characteristics of «space» solar cells based porous silicon in the Comsol Multiphysics package

Abstract: To analyze the characteristics of solar modules based on porous silicon involved in the flight experiment aboard a small spacecraft AIST 2D, the method of computer simulation of solar cell characteristics was used. The paper presents the procedure for developing a simulation model of photovoltaic modules in Comsol Multyphysics. The developed model allows us to investigate the current-voltage and voltage-watt characteristics of solar modules and determine the main parameters. The discrepancy between the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In real cells, power is dissipated through a series resistance 'R s ' created due to the ohmic contact in the front surface and shunt resistance 'R sh ' due to leakage current. Therefore, for a practical solar cell, the equivalent circuit includes 'R sh ' added in parallel with the diode and 'R s ' added in series with the load as given below, Figure 6 [31][32][33]. Therefore, the above equation can be written as follows:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In real cells, power is dissipated through a series resistance 'R s ' created due to the ohmic contact in the front surface and shunt resistance 'R sh ' due to leakage current. Therefore, for a practical solar cell, the equivalent circuit includes 'R sh ' added in parallel with the diode and 'R s ' added in series with the load as given below, Figure 6 [31][32][33]. Therefore, the above equation can be written as follows:…”
mentioning
confidence: 99%
“…The results showed that higher PV efficiencies can be achieved by increasing the mobility and carriers' lifetime while decreasing the surface recombination velocities [111][112][113]. Moreover, [31] developed a simulation model of PV modules in COMSOL Multiphysics to investigate the I-V and P-V characteristics of p-n junction space solar modules based on porous Si. The difference between the PV electrical characteristics COMSOL results and the experimental data obtained does not exceed 5%.…”
mentioning
confidence: 99%